Case study: National Library Board Singapore: Delivering cost-effective service excellence through innovation and people - WIRTZ, Jochen (Institutional Knowledge at Singapore Management University, 2021)
The National Library Board (NLB) Singapore is a statutory board that managed to become a serial innovator. Its globally leading innovations in the library context include shelf-reading robots, and even entirely self-service libraries. NLB’s consistent focus on excellent service delivery reinforced its commitment to innovation. Key levers were effective strategic leadership, a smart innovation strategy that made heavy use of technology — such as app-delivered self-service technologies, crowdsourcing, and robotics — as well as a people-centric staff culture. NLB managed to co-create attractive libraries of the future together with different types of community members, such as volunteers and corporations, ushering in a new age of citizen involvement while also preparing both the library and the population of Singapore for the knowledge demands of the 21st century. This case study describes NLB’s drivers of successful innovation.